2018
DOI: 10.1038/sdata.2018.117
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable data and metadata management at the BD2K-LINCS Data Coordination and Integration Center

Abstract: The NIH-funded LINCS Consortium is creating an extensive reference library of cell-based perturbation response signatures and sophisticated informatics tools incorporating a large number of perturbagens, model systems, and assays. To date, more than 350 datasets have been generated including transcriptomics, proteomics, epigenomics, cell phenotype and competitive binding profiling assays. The large volume and variety of data necessitate rigorous data standards and effective data management including modular da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…For example, the Library of Integrated Network-based Cellular Signatures (LINCS) project, a multicenter NIH-funded program, created a comprehensive library of molecular signatures supporting data integration, modeling and analysis methodologies. 49 Broad sharing of genomic-and health-related data requires proper governance and security. 50 In the context of stem cell research, data and sample sharing represent a scientific and ethical challenge to ensure appropriate protection of individual interests as well as maintaining public trust.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Library of Integrated Network-based Cellular Signatures (LINCS) project, a multicenter NIH-funded program, created a comprehensive library of molecular signatures supporting data integration, modeling and analysis methodologies. 49 Broad sharing of genomic-and health-related data requires proper governance and security. 50 In the context of stem cell research, data and sample sharing represent a scientific and ethical challenge to ensure appropriate protection of individual interests as well as maintaining public trust.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in screening technologies, including detection sensitivity and throughput, robotics, and data science, have enabled many large scale data generation projects during the last two decades [26,30]. Examples of publicly funded research consortia focused on small molecule discovery and characterization include the Molecular Libraries Program (MLP) [39], the Tox21 screening program, the Psychoactive Drug Screening Program (PDSP) [40], the Library of Integrated Network-based Cellular Signatures (LINCS) [21], and Illuminating the Druggable Genome (IDG) [41,42]. While such individual projects can have enormous scientific impact, their combined value and impact may yet be considerably larger, because integrated “big data” have potential to provide new insights that cannot be obtained from individual datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics, transcriptomics, metabolomics, and target-based cell and biochemical screening data can have compatible metadata enabling their integrative analysis. We recently illustrated best practices of metadata management in another large scale data generation project [21], the Library of Integrated Network-based Cellular Signatures (LINCS) [22]. To that end, we endeavored to further improve the reusability of the Tox21 data and illustrate newfound usability after fully annotating assay information by established reference ontologies followed by aggregating the data to enable specific actionable insights.…”
Section: Introductionmentioning
confidence: 99%
“…Such mappings would enable cross-referencing to major public chemical databases to enrich the annotations by providing additional annotations, such as mechanism of actions, targets, disease associations, clinical phase status, and synonyms. It has been shown that such data submission systems, with deep metadata annotations that utilize established terminologies and ontologies, contribute to interoperability and reusability of the data (Stathias et al 2018 ).…”
Section: Future Perspectivesmentioning
confidence: 99%